General Iterative Scheme for Split Mixed Equilibrium Problems, Variational Inequality Problems and Fixed Point Problems in Hilbert Spaces - Deepho, Jitsupa; Kumam, Poom (Communications in Mathematics and Applications, 2020)
The purpose in this paper is to study the strong convergence of general iterative scheme to find a common element of the set of a finite family of nonexpansive mappings, the set of solutions of variational inequalities for a relaxed cocoercive mapping and the set of solutions of split mixed equilibrium problem. Our results extend recent results announced by many others.